2015
DOI: 10.1186/s13065-015-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

A concise synthesis of Fingolimod: an orally available drug for treating multiple sclerosis

Abstract: A concise route for the synthesis of Fingolimod is reported. Starting from n-octylbenzene and 3-nitropropionic acid, a sequence of reactions consisting of Friedel-Crafts acylation, reduction, and double Henry reaction, followed by hydrogenation were applied to prepare Fingolimod with a yield of 31%, and an overall atom economy of 82.7%.Graphical AbstractStarting from 3-nitropropanyl chloride, Fingolimod was obtained in 4 steps with an overall yield of 31%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The developed procedure showed that TES could reduce only the carbonyl group without cleaving the halogen. Subsequent contributions reported the selectivities of TES/TFA 30 and TES/B(C 6 F 5 ) 3 systems 27 (see Scheme 16) for similar ketones bearing nitroalkyl and alkoxy substituents (51b), respectively. It is worth mentioning that a TES/Pd(OAc) 2 /TfOSiR 3 catalytic system was employed for the safe conversion of C=S bonds in the syntheses of imidazolinium salts, which are potent ligands and catalysts.…”
Section: Scheme 13 Tes/tfa-mediated Reduction Of Ketones To Alcoholsmentioning
confidence: 99%
“…The developed procedure showed that TES could reduce only the carbonyl group without cleaving the halogen. Subsequent contributions reported the selectivities of TES/TFA 30 and TES/B(C 6 F 5 ) 3 systems 27 (see Scheme 16) for similar ketones bearing nitroalkyl and alkoxy substituents (51b), respectively. It is worth mentioning that a TES/Pd(OAc) 2 /TfOSiR 3 catalytic system was employed for the safe conversion of C=S bonds in the syntheses of imidazolinium salts, which are potent ligands and catalysts.…”
Section: Scheme 13 Tes/tfa-mediated Reduction Of Ketones To Alcoholsmentioning
confidence: 99%
“…Different synthetic pathways could be used to manufacture fingolimod, which may add other potential process‐related impurities depending on the manufacturing process, starting materials and intermediates used (Adachi et al, 1995; Kiuchi et al, 2000; Durand et al, 2000; Kalita et al, 2001; Seidel et al, 2004; Sugiyama et al, 2005; Kim et al, 2006; Matsumoto et al, 2008; Calzavara & McNulty, 2011; Feng et al, 2012; Kandagatla et al, 2013; Shaikh et al, 2015; Yan et al, 2015; Balaev et al, 2017; Maruthi Raju et al, 2017a, 2017b; Lin et al, 2018; Vinigari et al, 2019). To the prove the absence of additional impurities and ensure drug substance quality according to International Conference on Harmonization (ICH) guideline Q3A, potential process‐related impurities should be evaluated and pharmacopoeia methods should be validated by the addition of these impurities, or in‐house methods should be developed and validated including all pharmacopoeia and in‐house impurities.…”
Section: Introductionmentioning
confidence: 99%